Kajian Androgyny Karya Deden Siswanto - Dede Ananta Kurniawan (JURNAL RUPA, 2021)
Androgyny is a concept that refers to gender and gender, where the tendency of masculine and feminine traits is seen from the dominant feature in a person. The androgynous style by designer Deden Siswanto applies this style in his design collection. This study aims to analyze the androgyny style developed by Deden Siswanto and its application to his design collection. This study uses a descriptive-analytical method with a qualitative approach with data collection through field observations, interviews with resource persons, documentation studies of fashion design collections by Deden Siswanto. Based on the results of data analysis, the application of the androgynous style in Deden Siswanto's collections can be seen in the clothing sections, such as fashion silhouettes, colors, types of clothing, and their mixes. Thus Deden Siswanto designed his collection with adjustments to the target market and the character of the design. Thus Deden Siswanto designed his collection with adjustments to the target market and the nature of the design. For this reason, the idea and creativity of androgynous styles, both masculine and feminine in a designer's work, tend to be developed and adapted differently according to the designer's character.